2013
DOI: 10.1021/om400584f
|View full text |Cite
|
Sign up to set email alerts
|

High Oxidation State Molybdenum Imido Heteroatom-Substituted Alkylidene Complexes

Abstract: Reactions between Mo(NAr)(CHR)(Me2Pyr)-(OTPP) (Ar = 2,6-i-Pr2C6H3, R = H or CHCMe2Ph, Me2Pyr = 2,5-dimethylpyrrolide, OTPP = O-2,3,5,6-Ph4C6H) and CH2=CHX where X = B(pin), SiMe3, N-carbazolyl, N-pyrrolidinonyl, PPh2, OPr, or SPh lead to Mo(NAr)(CHX)-(Me2Pyr)(OTPP) complexes in good yield. All have been characterized through X-ray studies (as an acetonitrile adduct in the case of X = PPh2). The efficiencies of metathesis reactions initiated by Mo(NAr)(CHX)(Me2Pyr)(OTPP) complexes can be rationalized on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The catalytically active halo-substituted alkylidenes derived from Mo-4c can thus deliver the necessary activity (e.g., vs. Ru - 2-4 or W-1 ) but not at the expense of catalyst lifetime [e.g., vs. bis(alkoxide) Mo-1 ]. The Mo center in a MAP system is likely electron-deficient enough to prevent metal-carbide formation 34 , and yet, unlike Ru carbenes, π-electron donation by a halide alkylidene substituent 50 does not hamper reactivity. Another noteworthy aspect is the design of reactions where the use of a dissymmetric Z -bromo-fluoroethene leads to the predominant or exclusive formation of fluoro-substituted alkenes (vs. the bromo derivatives); this way, an easy-to-handle and readily accessible reagent can be used instead of the costly and impractical fluoro-olefin alternatives (e.g., vinyl fluoride or Z -1,2-difluoroethene).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytically active halo-substituted alkylidenes derived from Mo-4c can thus deliver the necessary activity (e.g., vs. Ru - 2-4 or W-1 ) but not at the expense of catalyst lifetime [e.g., vs. bis(alkoxide) Mo-1 ]. The Mo center in a MAP system is likely electron-deficient enough to prevent metal-carbide formation 34 , and yet, unlike Ru carbenes, π-electron donation by a halide alkylidene substituent 50 does not hamper reactivity. Another noteworthy aspect is the design of reactions where the use of a dissymmetric Z -bromo-fluoroethene leads to the predominant or exclusive formation of fluoro-substituted alkenes (vs. the bromo derivatives); this way, an easy-to-handle and readily accessible reagent can be used instead of the costly and impractical fluoro-olefin alternatives (e.g., vinyl fluoride or Z -1,2-difluoroethene).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the chloro-alkylidene generated in the metathesis is of low stability, and because mRCM's are performed under dilute conditions, the alkylidene decomposes before it can react with another olefin. Previous studies showed that pinacolatoboryl-(B(pin)) substituted alkylidenes were less reactive than their carbon counterparts, [110] so these were …”
Section: 1002/anie201704686 Angewandte Chemie International Editionmentioning
confidence: 99%
“…The vast majority of metathesis reactions involve M=CHR intermediates in which R is carbon-based or H. Some alkylidenes in which R is a heteroatom have now been isolated and appear to react with olefins in a metathesis fashion. 35 Much remains to be done in terms of developing catalysts for metathesis reactions that yield directly functionalized olefins, especially those that can be employed subsequently in catalytic reactions that are not metathesis-based. 36 …”
Section: Organic Synthesismentioning
confidence: 99%